A typology of interdisciplinary collaborations: insights from agri-food transformation research - Benjamin Hofmann; Ueli Reber; Priska Ammann; Julia Dötzer; Jennifer Mark; Chloe McCallum; Milena Wiget; Lucca Zachmann (Sustainability Science, 2025)
To understand complex societal transformations, scholars have called for more interdisciplinary research in which researchers from various disciplines collaborate. To support the implementation of such collaborations, we introduce a novel typology of interdisciplinary collaborations developed from the literature and from structured reflection on our own research experience. The typology distinguishes (I) common base, (II) common destination, and (III) sequential link type of interdisciplinary collaborations. Common base refers to an interdisciplinary collaboration at one research stage that later separates into parallel disciplinary work; common destination to a collaboration where separate disciplinary work feeds into joint interdisciplinary work at the next stage; and sequential link to a completed stage of disciplinary research that provides the basis for research in another discipline. We illustrate the typology with a case study of interdisciplinary collaborations in a research project that studied the potential for an evidence-based transformation of agricultural pesticide governance. The project involved researchers from seven natural, health, and social science disciplines who developed a process for forming and maintaining interdisciplinary collaborations. We provide five examples of interdisciplinary collaborations from the project, explaining for each its practical design and implementation, its contribution to overall research goals, and related opportunities and challenges. The examples show that the typology can systematize the thinking about interdisciplinary collaborations and enable critical reflection about interdisciplinary research design and implementation. Based on our reflections as early-career researchers, we conclude with lessons that can inform future interdisciplinary research projects on agri-food transformation and beyond.

Roles of researchers in inter- and transdisciplinary sustainability research: a reflection tool - Benjamin Hofmann; Hanna Salomon; Sabine Hoffmann (Sustainability Science, 2025)
Inter- and transdisciplinary (ITD) research is increasingly called for and supported to promote sustainable transformation through knowledge co-production, knowledge integration, and solution development. The paper explores what is needed to support researchers in reflecting on their new roles in ITD research. We introduce a reflection tool that makes the growing literature on researchers’ roles in sustainability science applicable to ITD projects. Its design is based on the arguments that each researcher can have several roles within one research project and that focusing on a few key roles increases clarity compared to differentiating many specialized roles. The tool consists of (1) a researcher survey that operationalizes six prominent roles (traditional scientist, self-reflexive scientist, knowledge integrator, knowledge broker, process facilitator, and change agent), (2) a visualization of role profiles from the survey, and (3) a set of reflection questions on related opportunities, challenges, and coping strategies on individual and project level. We empirically applied the tool in two ITD research projects focused on sustainable food production and water and forest ecosystem management. Comparative application of the tool yielded diverse role profiles of researchers in both projects, with different patterns for senior and junior researchers as well as natural and social scientists. The reflection produced a collection of opportunities, challenges, and coping strategies that corroborates and extends insights from ITD literature. We discuss how the tool triggers multi-dimensional reflection on roles (individual and project level, role combinations, self-perception and external perception) and outline opportunities for further strengthening such reflection in ITD research.

Nitrate exposure from drinking water and dietary sources among Iowa farmers using private wells - Timothy G. Skalaban; Darrin A. Thompson; Jessica M. Madrigal; Benjamin C. Blount; Maria Morel Espinosa; Dana W. Kolpin; Nicole C. Deziel; Rena R. Jones; Laura Beane Freeman; Jonathan N. Hofmann; Mary H. Ward (Science of The Total Environment, 2024)

Barriers to evidence use for sustainability: Insights from pesticide policy and practice - Benjamin Hofmann; Karin Ingold; Christian Stamm; Priska Ammann; Rik I. L. Eggen; Robert Finger; Samuel Fuhrimann; Judit Lienert; Jennifer Mark; Chloe McCallum; Nicole Probst-Hensch; Ueli Reber; et al. (Ambio, 2023)
Calls for supporting sustainability through more and better research rest on an incomplete understanding of scientific evidence use. We argue that a variety of barriers to a transformative impact of evidence arises from diverse actor motivations within different stages of evidence use. We abductively specify this variety in policy and practice arenas for three actor motivations (truth-seeking, sense-making, and utility-maximizing) and five stages (evidence production, uptake, influence on decisions, effects on sustainability outcomes, and feedback from outcome evaluations). Our interdisciplinary synthesis focuses on the sustainability challenge of reducing environmental and human health risks of agricultural pesticides. It identifies barriers resulting from (1) truth-seekers’ desire to reduce uncertainty that is complicated by evidence gaps, (2) sense-makers’ evidence needs that differ from the type of evidence available, and (3) utility-maximizers’ interests that guide strategic evidence use. We outline context-specific research–policy–practice measures to increase evidence use for sustainable transformation in pesticides and beyond.

Phenotyping in the era of genomics: MaTrics—a digital character matrix to document mammalian phenotypic traits - Clara Stefen; Franziska Wagner; Marika Asztalos; Peter Giere; Peter Grobe; Michael Hiller; Rebecca Hofmann; Maria Jähde; Ulla Lächele; Thomas Lehmann; Sylvia Ortmann; Benjamin Peters; et al. (Mammalian Biology, 2022)
A new and uniquely structured matrix of mammalian phenotypes, MaTrics ( Ma mmalian Tr aits for Comparative Genom ics ) in a digital form is presented. By focussing on mammalian species for which genome assemblies are available, MaTrics provides an interface between mammalogy and comparative genomics. MaTrics was developed within a project aimed to find genetic causes of phenotypic traits of mammals using Forward Genomics. This approach requires genomes and comprehensive and recorded information on homologous phenotypes that are coded as discrete categories in a matrix. MaTrics is an evolving online resource providing information on phenotypic traits in numeric code; traits are coded either as absent/present or with several states as multistate. The state record for each species is linked to at least one reference (e.g., literature, photographs, histological sections, CT scans, or museum specimens) and so MaTrics contributes to digitalization of museum collections. Currently, MaTrics covers 147 mammalian species and includes 231 characters related to structure, morphology, physiology, ecology, and ethology and available in a machine actionable NEXUS-format*. Filling MaTrics revealed substantial knowledge gaps, highlighting the need for phenotyping efforts. Studies based on selected data from MaTrics and using Forward Genomics identified associations between genes and certain phenotypes ranging from lifestyles (e.g., aquatic) to dietary specializations (e.g., herbivory, carnivory). These findings motivate the expansion of phenotyping in MaTrics by filling research gaps and by adding taxa and traits. Only databases like MaTrics will provide machine actionable information on phenotypic traits, an important limitation to genomics. MaTrics is available within the data repository Morph·D·Base ( www.morphdbase.de ).

In Vitro Ceramic Scaffold Mineralization: Comparison Between Histological and Micro-Computed Tomographical Analysis - Benjamin W. Thimm; Oliver Wechsler; Marc Bohner; Ralph Müller; Sandra Hofmann (Annals of Biomedical Engineering, 2013)